Reliability of waveform analysis as an adjunct to loss of resistance for thoracic epidural blocks - Prangmalee Leurcharusmee (2018)
Copyright © 2015 American Society of Regional Anesthesia and Pain Medicine. Background: The epidural space is most commonly identified with loss of resistance (LOR). Although sensitive, LOR lacks specificity, as cysts in interspinous ligaments, gaps in ligamentum flavum, paravertebral muscles, thoracic paravertebral spaces, and intermuscular planes can yield nonepidural LOR. Epidural waveform analysis (EWA) provides a simple confirmatory adjunct for LOR. When the needle is correctly positioned inside the epidural space, measurement of the pressure at its tip results in a pulsatile waveform. In this observational study, we set out to assess the sensitivity, specificity, as well as positive and negative predictive values of EWA for thoracic epidural blocks. Methods: We enrolled a convenience sample of 160 patients undergoing thoracic epidural blocks for thoracic surgery, abdominal surgery, or rib fractures. The choice of patient position (sitting or lateral decubitus), approach (midline or paramedian), and LOR medium (air or normal saline) was left to the operator (attending anesthesiologist, fellow, or resident). After obtaining a satisfactory LOR, the operator injected 5 mL of normal saline through the epidural needle. A sterile tubing, connected to a pressure transducer, was attached to the needle to measure the pressure at the needle tip. A 4-mL bolus of lidocaine 2% with epinephrine 5 ìg/mL was then administered and, after 10 minutes, the patient was assessed for sensory blockade to ice. Results: The failure rate (incorrect identification of the epidural space with LOR) was 23.1%. Of these 37 failed epidural blocks, 27 provided no sensory anesthesia at 10 minutes. In 10 subjects, the operator was unable to thread the catheter through the needle. When compared with the ice test, the sensitivity, specificity, and positive and negative predictive values of EWAwere 91.1%, 83.8%, 94.9%, and 73.8%, respectively. Conclusions: Epidural waveform analysis (with pressure transduction through the needle) provides a simple adjunct to LOR for thoracic epidural blocks. Although its use was devoid of complications, further confirmatory studies are required before its routine implementation in clinical practice.